Recent Publications (Quarterly Journal of Economics, 1962)
Recent Publications Get access The Quarterly Journal of Economics, Volume 76, Issue 1, February 1962, Pages 167–171, https://doi.org/10.1093/qje/76.1.167 Published: 01 February 1962